Synthesis And Characterization Of Chlorine-Free Polycyclotriphosphazene As Adhesive For Glass - Ponnusamy, Rajeswary (2009)

(untitled)
The halogen-free phosphazene-based polymeric adhesive was synthesized via two separate steps. The first step involved the reaction of hexachlorocyclotriphosphazene with bisphenol A in the presence of dried triethylamine that afforded, after isolation and purification, a slightly yellowish solid polymer that is designated as P1 (chlorine-bound poly[2,2-di(p hydroxophenyl)propane]cyclotriphosphazene). In the second step, P1 was reacted with ethyl 4-hydroxybenzoate to obtain a white solid polymer that is designated as P2 (chlorine-free poly[2,2-di(p hydroxophenyl)propane]cyclotriphosphazene).